1982
DOI: 10.1161/01.cir.66.5.905
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous transluminal coronary angioplasty immediately after intracoronary streptolysis of transmural myocardial infarction.

Abstract: SUMMARY Percutaneous transluminal coronary angioplasty (PTCA) was performed in 21 patients with acute myocardial infarction (AMI) treated by intracoronary infusion of streptokinase within 8 hours after the onset of symptoms. Streptolysis therapy began a mean of 3.6 1.2 hours (±+ SD) after the onset of symptoms. The vessel was occluded in 14 patients and highly stenosed in seven. After the infusion of 67,300 + 63,200 IU of streptokinase over 26.1 21.5 minutes, patency of the occluded vessels was reached.PTCA as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
0
5

Year Published

1984
1984
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 294 publications
(45 citation statements)
references
References 20 publications
0
40
0
5
Order By: Relevance
“…2 In contrast to this line of reasoning, several anatomic studies3-' have shown that a substantial percentage of lesions associated with vessel thrombosis and acute myocardial infarction are moderate in severity. The complexity of this issue is further compounded by the fact that there are at least three reasons why the appearance of lesions immediately after streptokinase reper-clude the following: (1) unlysed thrombi may be associated with the stenosis, (2) there may be coronary spasm at the site of the stenosis that is resistant to traditional vasodilatory therapy, and (3) there may be acute plaque rupture that may "remodel" over a period of days or weeks.…”
mentioning
confidence: 96%
“…2 In contrast to this line of reasoning, several anatomic studies3-' have shown that a substantial percentage of lesions associated with vessel thrombosis and acute myocardial infarction are moderate in severity. The complexity of this issue is further compounded by the fact that there are at least three reasons why the appearance of lesions immediately after streptokinase reper-clude the following: (1) unlysed thrombi may be associated with the stenosis, (2) there may be coronary spasm at the site of the stenosis that is resistant to traditional vasodilatory therapy, and (3) there may be acute plaque rupture that may "remodel" over a period of days or weeks.…”
mentioning
confidence: 96%
“…This operation was first carried out in 1982 by Meyer and colleagues in Germany. 30 From then until now a heated debate has existed over which of the 2 methods of reperfusion provides the greatest benefit for the management of a patient with an acute myocardial infarction. 31 More than 2 dozen randomized, controlled trials have been undertaken since the initial study reported 15 years ago by O'Neil and colleagues 32 in an attempt to resolve this dispute.…”
Section: Contributions Of the Eightiesmentioning
confidence: 99%
“…Studies have also been done employing percutaneous transluminal angioplasty after thrombolysis (Gold et al, 1984;Meyer et al, 1982;Papapiotro et al, 1985). An advantage of ICSK is that angioplasty, if indicated, can potentially be performed immediately after thrombolysis.…”
Section: Percutaneous Transluminal Coronary Angioplasty Following Thrmentioning
confidence: 99%